Towards new TB vaccines - Brazier, B; McShane, H (Springer, 2020)
Mycobacterium tuberculosis remains the leading cause of death attributed to a single infectious organism. Bacillus Calmette-Guerin (BCG), the standard vaccine against M. tuberculosis, is thought to prevent only 5% of all vaccine-preventable deaths due to tuberculosis, thus an alternative vaccine is required. One of the principal barriers to vaccine development against M. tuberculosis is the complexity of the immune response to infection, with uncertainty as to what constitutes an immunological correlate of protection. In this paper, we seek to give an overview of the immunology of M. tuberculosis infection, and by doing so, investigate possible targets of vaccine development. This encompasses the innate, adaptive, mucosal and humoral immune systems. Though MVA85A did not improve protection compared with BCG alone in a large-scale clinical trial, the correlates of protection this has revealed, in addition to promising results from candidate such as VPM1002, M72/ASO1E and H56:IC31 point to a brighter future in the field of TB vaccine development.